Longitudinal alterations in morphological brain networks and cognitive function in common-type COVID-19: a 3-month follow-up study - Ying Liu; Ying Liu; Bei Peng; Haixia Qin; Kaixuan Zhou; Shihuan Lin; Yinqi Lai; Lingyan Liang; Gaoxiong Duan; Xiaocheng Li; Xiaoyan Zhou; Yichen Wei; et al. (Frontiers in Neurology)
PurposeTo investigate the morphological network and cognitive function of patients with common-type coronavirus disease 2019 (COVID-19) during the acute phase, and examine dynamic changes at 3-month follow-up.MethodsAt baseline, high-resolution T1-weighted imaging was conducted in 35 patients with COVID-19 and 40 healthy controls; 22 patients were reassessed at 3 months. All patients underwent cognitive assessments. Individual morphological brain networks were constructed using grey matter volume similarity, and topological properties were analyzed using graph theory. We used an independent sample t-test at baseline and a paired sample t-test to compare the 3-month follow-up with the acute phase, with false discovery rate corrections (p < 0.05).ResultsIn the acute phase, patients exhibited increased subcortical network (SCN) connectivity, and reduced connectivity between the frontoparietal network (FPN) and limbic network (LN), the SCN and dorsal/ventral attention network (DAN/VAN), and the LN and DAN. At follow-up, SCN connectivity remained elevated, with partial recovery in SCN-DAN/VAN and LN-DAN connectivity, and significant FPN-LN improvements. Enhanced global efficiency and reduced path length indicated improved network integration. Additionally, digit symbol substitution test and verbal fluency test scores improved over time.ConclusionCOVID-19 induces short-term disruptions in cognition-related morphological subnetworks, with subcortical networks compensating for these changes. Significant recovery in FPN-LN connectivity and partial restoration of other networks highlight the plasticity of the brain and suggest that FPN-LN connectivity is a potential neuroimaging marker for cognitive recovery.